The old man and the sea - Hemingway, Ernest, 1899-1961. (London : Arrow Books, 2000)
An old fisherman battles the sea and sharks to bring home the giant marlin he caught.
Young Adult
Keywords: Fishers -- Cuba -- Fiction; Friendship -- Fiction; Older men -- Cuba -- Fiction; Allegories; Chinese language; Elderly men -- Cuba -- Fiction; Fishers -- Fiction; Cuba -- Fiction